Knowledge and Attitude of Nurses about the Nursing Process in Selected Public Hospitals in South-West Ethiopia - Adraro, Zerihun; Cherkos, Adugna (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: The nursing process is a standard for delivering individualized, continuing nursing care using standardized nursing language and helps improve the relationship between nurses and patients, allowing use of available resources for patient care and creating good interaction between practitioners. The aim of this study is to assess nurses ' knowledge and attitude about the nursing process in selected public hospitals in southwestern Ethiopia. Methods: An institution-based cross-sectional descriptive study was conducted in three selected public hospitals in south-west Ethiopia using pre-tested self-administered questionnaires from March-April 2016. With simple random sampling, a total of 138 nurses from the three hospitals were included in the study. Data were categorized, coded, entered in version 7 of Epidemiological Information (EPI info) and exported for analysis to the Statistical Package for Social Science (SPSS) version 20. Descriptive statistics have been used to describe the variables of the study. Results: Nurses ' knowledge of the nursing process was found to be poor as six out of ten nurses had poor knowledge and five out of ten nurses had a positive attitude towards the nursing process. Conclusions: The majority of nurses had poor nursing knowledge and nearly half of nurses had a positive attitude to the nursing process.